2018
DOI: 10.1371/journal.pone.0191463
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the risks of prevention of mother to child transmission (PMTCT) of HIV services in Kibera, Kenya: Barriers to engaging and remaining in care

Abstract: Within the first year of implementation, 43% of women who tested HIV positive at their first antenatal care visit were no longer retained and being followed in the free prevention of mother to child transmission (PMTCT) of HIV program offered by the Kenyan Ministry of Health and Médecins Sans Frontières in the informal settlement of Kibera, Nairobi. This study aimed to explore barriers to enrolling and remaining engaged in PMTCT services throughout the pregnancy and postpartum periods. Qualitative data from 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 23 publications
1
37
0
Order By: Relevance
“…A recent study done in Kenya reported that men are at times unaware of PMTCT services, yet their understanding is the platform for rendering support to a partner. 27 Spousal support and disclosure of an HIV status is influenced by the strength of the relationship with solid relationships creating a safe environment for disclosure. 27 Women are key in spousal support, because in some instances, women do not want their partners accompanying them for PMTCT services, which hinders male involvement.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study done in Kenya reported that men are at times unaware of PMTCT services, yet their understanding is the platform for rendering support to a partner. 27 Spousal support and disclosure of an HIV status is influenced by the strength of the relationship with solid relationships creating a safe environment for disclosure. 27 Women are key in spousal support, because in some instances, women do not want their partners accompanying them for PMTCT services, which hinders male involvement.…”
Section: Introductionmentioning
confidence: 99%
“…While the item (iv) The man supports his partner’s antenatal visits financially corresponds to ‘Economic support’. In Kenya, [20] a previous study defined male partner involvement as both active and passive. Active involvement could include attending ANC/PMTCT appointments at the clinic with his partner.…”
Section: Discussionmentioning
confidence: 99%
“…In the framework of prevention of mother-to-child transmission (PMTCT), male partner involvement is usually aimed at the health needs of the mother and infant, such as support for mothers’ antenatal HIV testing, uptake of Nevirapine, and formula-feeding or exclusive breastfeeding [14, 16]. Studies have suggested ways to define male partner involvement (MI) and its determinants in a PMTCT setting [17–20]. However, the descriptions focus on clinic attendance and couple counselling and testing [2123], and in other instances, remain indefinite and vary within different populations and contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the findings of our study and other studies [35][36][37][38] we therefore emphasize the need for a multi-level intervention targeted at improving working conditions and reducing health system deficiencies to promote HCP professional development and quality of patient care. To improve professionalization of HCPs, we recommend training on personalised, culturally and contextually appropriate care [39,40], which can be included in university curricula for medical and nursing students and in the regular in-service training for HCPs. A more personalised approach to PMTCT and maternity care will make HCPs not only an advocate for babies, but also an advocate for mothers.…”
Section: Discussionmentioning
confidence: 99%